MALAY WOMEN IN HISTORICAL STUDIES: A BIBLIOMETRIC REVIEW - Ahmad, Nor Aisyah; Zubir, Zuliana; Zainal Abidin, Afifah (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This study presents a bibliometric analysis examining global research trends on Malay women in historical studies from 2000 to 2025. Addressing the limited mapping of scholarly output in this area, the analysis focuses on identifying publication patterns, subject distributions, influential authors, dominant keywords, and international collaboration networks. Using the keywords "Malay," "women," and "historical studies," data collection was conducted through the Scopus database. The search process applied strict inclusion criteria, targeting peer-reviewed journal articles in English within the Social Sciences and Arts and Humanities subject areas. After refining the dataset with OpenRefine software and visualizing relationships using VOSviewer, a total of 834 relevant documents were analyzed. The Scopus Analyzer tool further facilitated the identification of publication trends across the selected timeframe. Results indicate a steady increase in research output over the years, with a significant surge beginning in 2018 and peaking in 2023. The United States and the United Kingdom emerged as the leading contributors, while Malaysia showed gradual progress in domestic research participation. Subject area analysis revealed a dominant focus on Social Sciences and Arts and Humanities, accounting for more than 93% of total publications. Keyword co-occurrence mapping highlighted themes such as gender, feminism, womanhood, and identity, reflecting growing academic interest in intersectionality and postcolonial perspectives. Co-authorship analysis showed strong international collaborations, particularly among Western countries and Southeast Asian regions. Despite the increasing volume of research, limitations exist, especially concerning the reliance on a single database and the exclusion of non-English publications. These findings provide a comprehensive overview of the scholarly landscape and highlight the need for more diversified and locally-driven research on Malay women in historical contexts. The study demonstrates the relevance of bibliometric methods in tracking research development and offers a foundational reference for future investigations in this field.